Dendritic cells in inborn errors of immunity - Gupta, Sudhir; Agrawal, Anshu (Frontiers in Immunology, 2023)
Dendritic cells (DCs) are crucial cells for initiating and maintaining immune response. They play critical role in homeostasis, inflammation, and autoimmunity. A number of molecules regulate their functions including synapse formation, migration, immunity, and induction of tolerance. A number of IEI are characterized by mutations in genes encoding several of these molecules resulting in immunodeficiency, inflammation, and autoimmunity in IEI. Currently, there are 465 Inborn errors of immunity (IEI) that have been grouped in 10 different categories. However, comprehensive studies of DCs have been reported in only few IEI. Here we have reviewed biology of DCs in IEI classified according to recently published IUIS classification. We have reviewed DCs in selected IEI in each group category and discussed in depth changes in DCs where significant data are available regarding role of DCs in clinical and immunological manifestations. These include severe immunodeficiency diseases, antibody deficiencies, combined immunodeficiency with associated and syndromic features, especially disorders of synapse formation, and disorders of immune regulation.